Stability Constants of Cu(II)/Ni(II) of Binary Chelates with 4-Hydroxypicolinic Acid N-Oxide in Aquo-Organic Media. - VENKATARAMANA REDDY, CH.; BALRAJ, G.; RAM REDDY, M.G. (Asian Journal of Chemistry, 2010)
The proton ligand constants of 4-hydroxypicolinic acid N-oxide and the complexation equilibria of corresponding binary chelates of Cu(II) and Ni(II) have been measured at 30º ± 1ºC and 0.1 M ionic strength in varying percentages of dioxane-water, acetone-water, ethanol-water and isopropanol-water media. The results are discussed with reference to the change in dielectric constants of water in the presence of organic solvent, change in the structuredness of water, change in hydrogen bonding ability of the organic solvent in water, solvent basicity and proton solvation by organic solvent. The values have been compared with aqueous and mixed aqueous systems of picolinic acid N-oxide and 4-aminopicolinic acid N-oxide.